2004
DOI: 10.1161/01.cir.0000128862.34201.74
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Low-Dose Dobutamine Test Is Superior to Scar Quantification for the Prediction of Functional Recovery

Abstract: Background-Low-dose dobutamine challenge (DSMR) by MRI was compared with delayed enhancement imaging with Gd-DTPA (SCAR) as a predictor of improvement of wall motion after revascularization (RECOVERY). Methods and Results-In 29 patients with coronary artery disease (68Ϯ7 years of age, 2 women, 32Ϯ8% ejection fraction), wall motion was evaluated semiquantitatively by MRI before and 3 months after revascularization. SCAR and DSMR were performed before revascularization. The transmural extent of scar was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(160 citation statements)
references
References 30 publications
11
145
0
4
Order By: Relevance
“…Roes et al 54 commented that only 53% of segments with subendocardial scar with 1%-50% transmurality in the study of Kim et al 40 showed functional recovery. The addition of dobutamine stress CMR has been advocated in patients with 25%-75% transmurality to improve diagnostic performance 56 and is mentioned further below.…”
Section: Cmr Imagingmentioning
confidence: 99%
“…Roes et al 54 commented that only 53% of segments with subendocardial scar with 1%-50% transmurality in the study of Kim et al 40 showed functional recovery. The addition of dobutamine stress CMR has been advocated in patients with 25%-75% transmurality to improve diagnostic performance 56 and is mentioned further below.…”
Section: Cmr Imagingmentioning
confidence: 99%
“…An improvement of regional contractility during a continuous infusion of dobutamine at a dose of 10 µg/kg body weight/min or less has been shown to be a powerful predictor of functional recovery after revascularization therapy (54), and is a better predictor of LV functional recovery after revascularization than end-diastolic wall thickness (55). However, this method is limited by assessing viability indirectly through an assessment of function as a surrogate, which can be hampered in the presence of dysfunctional (eg, stunned or hibernating) tissue (56).…”
Section: Assessment Of Myocardial Viability In Ischemic Heart Diseasementioning
confidence: 99%
“…However, several studies showed that this may not be the case. Motoyasu et al [28] found low-dose dobutamine CMR to have a superior receiver operating characteristic (ROC) over the LGE technique (ROC area under the curve of 0.87 vs 0.78), whereas Wellnhofer et al [29] further showed that low-dose dobutamine CMR is particularly useful in predicting functional recovery in myocardial segments with transmural involvement by LGE of less than 75%. Similarly, Kaandorp et al [30] showed that low-dose dobutamine may improve viability assessment in patients with an intermediate degree of transmural involvement by LGE.…”
Section: Functional Reserve With Low-dose Dobutaminementioning
confidence: 99%